THE IMPACT OF GLOBALISATION ON THE DEVELOPMENT OF TOURISM WITHIN SOCIAL AND ECONOMIC CHANGES - Mihajlović, Iris; Krželj – Čolović, Zorica (European Scientific Journal, ESJ, 2014)
The paper provides a conceptual definition of the process of globalisation from different aspects and in the context of causality with dimensions of microenvironment and macro environment. The focus is on examining the intensity of impact of specific global trends on structural market changes in tourism demand within the macro environment at the level of demographic, cultural, political, technological and physical dimensions, and relations with the competition, which is a prerequisite to development of new trends in tourism. The viewpoints of numerous theoreticians engaged in this area which corroborate the main idea of the paper were taken into account. Globalisation and its effects overlap with various fields; therefore, the methods of explanation, description, and comparison were used in the research. The secondary research was conducted regarding the impact of technological changes on new trends in consumer behaviour in the tourism market, whereby the selected emitting markets in Europe were analysed in terms of intensity of application of innovative tools. Globalizationinduced changes in the environment give impetus to new trends in the tourism market which are evident in the emergence of new needs, behaviour of potential tourists and their preferences with regard to the choice of tourism products for which they show more or less interest.